Marek's Disease in Roosters in the Potiguar Semi-arid Region - Santana, Vanessa Silva; Prazeres Júnior, Fabiano Rocha; Oliveira, Letícia Batelli de; Torres, Ana Caroline Doyle; Martins, Nelson Rodrigo da Silva; Ecco, Roselene; Braga, Juliana Fortes Vilarinho (Acta Scientiae Veterinariae, 2022)
Background: Marek’s disease (MD) is a transmissible disease in chickens caused by Gallid alphaherpesvirus 2 (GaHV-2). The infection is characterized by lymphocyte cellular infiltrates in peripheral nerves and other organs and tissues, including the skin; which can lead to dysfunction causing progressive asymmetric paresis and complete spastic paralysis of body extremities. Dermatitis and cardiac myositis caused by GaHV-2 in free-range chickens has rarely been described in Brazil. This reports the occurrence of the disease with a confirmatory molecular diagnosis in free-range poultry showing signs of dermatitis, poor performance, and cachexia and no mortality in the semi-arid Potiguar region. Cases: Twenty roosters of the Shamo lineage, among a brood of 42 birds, had a history of progressive weight loss and skin lesions. Two birds with poor body condition, erythema, and scaling of the skin in the head and cervical regions were sent for clinical care. All birds were between 12 and 18 months of age and were vaccinated against Newcastle disease and avian yaws with only a few receiving vaccines against MD and Gumboro disease. According to the owner’s report, some birds were previously kept outdoors, and when they were transferred to a small shed with little air circulation, they began to develop clinical signs after approximately 15 days. The first signs of the disease were also reported to have appeared 2.5 months before clinical care and, in the meantime, several treatments were instituted without success. Owing to the general condition of the animals and inconclusive clinical suspicion, the birds were subjected to euthanasia and necropsy. Tissue samples were collected for histopathological and polymerase chain reaction analyses to search for the GaHV-2 DNA meq gene. The main clinicopathological findings were erythema (47%, 20/42) and desquamation of skin and mild, prominent white multifocal areas in the heart. Histopathology revealed infiltration of pleomorphic lymphoblastic cells in the skin, heart, and sciatic nerve. The amplification of the L-meq and meq oncoprotein genes in these organs and in the liver, confirmed the infection by GaHV-2, consistent with that of a field strain. Discussion: MD was confirmed based on the macroscopic and histological lesions, and with the detection of GaHV-2 DNA in the affected tissues. The unusual clinical presentation represented an initial challenge for diagnosis. The clinical history was important to lead to the suspicion of MD, as roosters initiated clinical signs 15 days after they were transferred to a small shed with poor air circulation. This probably favored the high viral concentration and disease transmission among susceptible birds in the brood because the feather follicle is the primary site of viral replication for transmission; and desquamation of infected epithelial cells favor airborne horizontal transmission to susceptible chickens. The roosters had not been vaccinated against MD, which probably favored the infection, as vaccination is known to be a fundamental approach for MD control for effective growth of the poultry industry. Clinical findings and lesions, together with viral molecular detection, were fundamental for the diagnosis, a premise for the application of adequate prevention and control measures for the disease in breeding. This is the first report of MD with a confirmatory molecular diagnosis in northeastern Brazil. Keywords: Viral diseases, Gallid alphaherpesvirus 2, neoplasms, polymerase chain reaction, histopathology.